Vielfalt des Religiösen Mittelalterliche Literatur im postsäkularen Kontext - Bernhardt, Susanne / Gebert (Literatur - Theorie - Geschichte, 2021)
The phenomena of religious pluralization in medieval texts can be observed not just in dramatic transgressions but also in subtle variations. The contributions in this volume sound out these intra- and interreligious spaces from the perspectives of semantics, narratology, and discourse and transmission history, providing new insights into the diversification of religious difference in the pre-modern period.